Perceptions of COVID–19-related Risks and Deaths Among Health Care Professionals During COVID-19 Pandemic in Pakistan: A Cross-sectional Study. (17th December 2021) - Hakim, Muhammad; Afaq, Saima; Khattak, Farhad ALi; Jawad, Mohammad; Ul Islam, Siraj; Ayub Rose, Muhammad; Shakeel Khan, Muhammad; Haq, Zia Ul
COVID-19 is an established challenge to the health care professionals (HCPs) having physical, emotional, and psychological repercussions. We determine the perceptions of Pakistani HCPs regarding the risks and deaths related to COVID-19. A cross-sectional study was conducted among HCPs throughout Pakistan from 16th February 2021 to 6th March 2021 by disseminating an online Google questionnaire via all possible social media platforms including WhatsApp, Facebook, Twitter, and emails. Out of total of 462 HCPs, 33.55% tested COVID-19 positive and 49.43% had received their first dose of COVID-19 vaccine. The proportion of HCPs worried about contracting COVID-19 was 46.97%. A total of 69.48% mentioned that doctors are at a higher risk of dying from COVID-19 infection compared to the general population. In a dichotomous analysis done for risk perception, 72.06% of doctors reported a high-risk perception of contracting COVID-19 in hospital settings. The main reasons identified to be associated with higher mortality amongst the HCPs, specifically doctors, included comorbidities (47.26%), working in high-risk wards (24.02%) and lack of adequate personal protective equipment (PPE) (28.72%). Using univariate and multivariate regression the HCPs tested positive rated two-fold high risk while performing professional duty during COVID-19 pandemic [unadjusted odds ratio (OR) (95% confidence interval (CI)): 2.23 (1.24–4.02), P = .007 ; adjusted OR (95% CI) 2.27 (1.22–4.19), P = .009 ]. In conclusion, Pakistani HCPs have significant COVID–19-related concerns and anxieties. The doctors perceived to be at a higher risk of dying with COVID-19, due to a variety of personal and professional reasons.